Grassland biomass balance in the European Alps: current and future ecosystem service perspectives - Jäger, Hieronymus; Peratoner, Giovanni; Tappeiner, Ulrike; Tasser, Erich (Ecosystem services, 2020)
[Display omitted] •Biomass supply and flow from grassland was modelled in the Alpine space area.•Biomass demand was assessed by integrating agricultural census statistics.•Energy balance is subject to strong regional differences.•Moderate climate change increases ecosystem service provision in the Northern Alps.•Extreme climate change decreases ecosystem service provision in the Eastern Alps. Grassland ecosystems provide the basis for grassland farming where climate and topography constrain the cultivation of crops. Current agricultural systems and their nutrient cycles are out of balance, due to the segregation of feed provision and consumption. However, knowledge on interlinkages between feed supply and demand is scarce and remains unclear on the transnational level. Here we show that the ecosystem service (ES) biomass production from grassland (BP), based on supply, flow and demand, varies spatially in the Alpine space and that climate change is contributing to the amplification of BP surpluses or deficits. We detected hotspots of BP flow and demand resulting in a negative energy balance: in the strongholds of animal husbandry, the demand exceeded the flow by up to 2,320 GJ ME ha−1. We found strong regional distinctions concerning climate change: Southern Alps will experience loss in BP provision, whereas low-elevation pre-Alps are predisposed to an increase of BP provision under moderate climate change. Livestock systems in mountains depend on grassland BP flows. We therefore recommend that our findings are integrated in a climate change adapted grassland management, which is crucial on the transnational level for the restoration and maintenance of regional nutrient cycles and BP provision.